2006
DOI: 10.1017/s0963548306007887
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Feedback Arc Set Problem is NP-Hard for Tournaments

Abstract: Answering a question of Bang-Jensen and Thomassen [4], we prove that the minimum feedback arc set problem is NP-hard for tournaments. A feedback arc set (fas) in a digraph D = (V , A) is a set F of arcs such that D \ F is acyclic. The size of a minimum feedback arc set of D is denoted by mfas(D). A classical result of Lawler and Karp [5] asserts that finding a minimum feedback arc set in a digraph is NP-hard. Bang-Jensen and Thomassen [4] conjectured that finding a minimum fas in a tournament is also NP-hard. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 4 publications
(4 reference statements)
0
77
0
Order By: Relevance
“…Bang-Jensen and Thomassen [5] conjectured that FAS is N P-complete even for tournaments. This conjecture was proved independently by at least four groups of researchers [1,2,8,9]. Interestingly, FAS is polynomial time solvable for planar digraphs [4,35] and trivially polynomial time solvable for undirected graphs.…”
Section: Feedback Arc and Vertex Set Problemsmentioning
confidence: 97%
“…Bang-Jensen and Thomassen [5] conjectured that FAS is N P-complete even for tournaments. This conjecture was proved independently by at least four groups of researchers [1,2,8,9]. Interestingly, FAS is polynomial time solvable for planar digraphs [4,35] and trivially polynomial time solvable for undirected graphs.…”
Section: Feedback Arc and Vertex Set Problemsmentioning
confidence: 97%
“…Dwork et al [10] prove the Rank Aggregation problem is NP-hard, even with as few as 4 input rankings. Recently, the FAS problem has been shown to be NP-hard even on unweighted tournaments [7]. Given this, it is natural to ask for an approximation algorithm which runs in polynomial time, yet is guaranteed to differ in cost from the optimal solution by a small factor.…”
Section: Hardness Of These Problemsmentioning
confidence: 99%
“…The latter are frequently easier to approximate (see below), and we show that this dichotomy extends to metric variants. There has been considerable recent interest in the approximability of the Consensus Clustering [1] and Rank Aggregation problems [6,20]. In particular, Bonizzoni et al showed that Consensus Clustering is APX-hard [5]; our paper is a response to this result.…”
Section: Introductionmentioning
confidence: 72%